ANALISIS MODEL FUNDRAISING ZAKAT, INFAK DAN SEDEKAH DI LEMBAGA ZAKAT - Nilda Susilawati (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2018)
Fundraising model of zalcat, infaq and alms on zakat institutions is done with different models, in accordance with the institutional management system, human resources and the scope of zaltat institutions are located. Fundraising model of zakat, infaq and alms is crucial to the success of institutions in collecting zakat, infak and alms from the community. In general, the model can be divided into two namely directly muzakki zakat institute to pay zakat and indirectly such as through the transfer, event, outlets, and application systems and zakat information. both models are very effective in collecting zakat, although it still needs improvement and development in its implementation in order to facilitate muzakki and able to attract the attention of muzakki in distributing zakat, infak and alms.